PEMBELAJARAN KARAKTER BERBASIS NILAI-NILAI PESATREN (Studi atas Pondok Pesantren Al-Is’af Kalabaan, Guluk-guluk Sumenep) - Mohammad Muchlis Solichin (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
Pesantren as a traditional islamic education institution runs the education system supported by values as the students’ characters. Keeping values of pesantren exists through teaching learning can strenghthen the taughness of the pesantren in keeping its existence in the society. This research is trying to analyze the pesantren’s values which become the characteristics of the santri and this values is developed in the teaching learning process. This research uses qualitative research with observation, interview, and documentation as the data collection procedure. From the result of the research, it can be seen that the santri’s characteristic values  which are defended in the education process in al-Is.’af Islamic boarding school are sincerity,survavibility, simplicity, asketism, spirit to teach and do worship to ALLAH.